Coadministration of Cardiomagnyl with Edarbi/Edarbi Clo in comparison with enteric-coated acetylsalicylic acid and renin-angiotensin-aldosterone system blockers in patients with hypertension and atherosclerotic cardiovascular diseases in the Russian Federation. Results of the CARAT study - F. T. Ageev; M. D. Smirnova; A. N. Kaftanov; D. V. Gavrilov (Российский кардиологический журнал)
Aim. To compare clinical outcomes in patients with hypertension and atherosclerotic cardiovascular diseases (CVDs) prescribed a combination of buffered acetylsalicylic acid (BA) (Cardiomagnyl®) + Azilsartan/Azilsartan+chlorthalidone (Edarbi/Edarbi Clo®) or enteric-coated acetylsalicylic acid (ECA) + reninangiotensin-aldosterone system (RAAS) blockers without diuretics or the most common combinations with diuretics within a real-world practice.Material and methods. Information accumulated in the predictive integrated analytics platform containing anonymized electronic medical records of 39935673 patients was used. According to the inclusion criteria, medical data from electronic medical records of 61696 patients were taken into the study. The data of 2120 patients with atherosclerotic CVDs were included and divided into 2 groups: BA (Cardiomagnyl® 75 mg) + Azilsartan or Azilsartan + chlorthalidone (main group) or ECA and other RAAS blockers and diuretics: ECA 100 mg + RAAS (angiotensin receptor blockers/angiotensin-converting enzyme inhibitors) ± hydrochlorothiazide/indapamide (comparison group). Propensity score matching was performed. Comparable groups were generated taking into account 11 parameters. The combined endpoint with 4-major adverse cardiovascular events (MACE) (myocardial infarction, ischemic stroke, hospitalization for CVD, all-cause death) was considered as the primary endpoint.Results. Comparison of the groups by achieving primary endpoint showed a significantly lower number of 4-MACE in patients of the main group. The risk of PCT was 28% (p=0,006) lower in the main group. In the main group, there were significantly fewer myocardial infarctions, ischemic strokes, any-cause deaths, as well as the risks of its achievement by 83%, 56% and 69%, respectively. There was a tendency towards a lower number of hospitalizations for CVD in the main group (p=0,08). In both groups, there was a significant (p<0,001) and comparable blood pressure decrease. Decrease in total cholesterol (Δ -0,26±1,0 mmol/l compared to Δ -0,13±1,1 mmol/l, p<0,001) and increase in low-density lipoprotein cholesterol (Δ 0,13±0,3 mmol/l compared to Δ 0,02±0,3 mmol/l, p<0,001) was significantly greater in the main group. Multidirectional changes of glucose levels were noted (p<0,001). In the main group, it decreases (Δ -0,14±2,2 mmol/l, p<0,001), while in the control group, on the contrary, it increases (Δ 0,08±2,2 mmol/l, p=0,001).Conclusion. Therapy for asthma in combination with azilsartan medoxomil/ azilsartan medoxomil + chlorthalidone (Cardiomagnyl® 75 mg + Edarbi/Edarbi Clo®) has shown greater efficacy in preventing cardiovascular events compared to therapy with a combination of ECA with other RAAS blockers and diuretics in real-world practice.